Pengembangan Desain Model Flipped Learning dalam Pembelajaran Daring - Rahmadana, Arini; Agnesa, Oki Sanda (Universitas Nusantara PGRI Kediri, 2023)
This research is a development research (R&D) which aims to develop a learning design using the Flipped Learning model in valid online conditions in the Educational Evaluation Engineering course. The development model used is the ADDIE model with reference to the learning design according to the philosophy of flipped learning. The development of Flipped Learning learning designs in online conditions produces several learning tools, namely 1) Guidelines for implementing Flipped Learning in online conditions, 2) Semester Lecture Plans for the Education Evaluation Techniques course using the Flipped Learning learning model, as well as Lecture Sheets for 16 meetings with Flipped Learning model. After being validated, a validation value of 3.36 was obtained from a scale of 4 and was stated to be very valid and could be used as a learning tool in educational evaluation techniques courses.